Hole design quality identification in laser aided additive manufacturing - Ahn, Il Hyuk (2019)
According to the increasing needs of three-dimensional printing technologies to satisfy high-level requirements, customization, and complicity, the quality of three-dimensional printed part becomes an important issue due to the layer-wise nature of additive manufacturing process. The objective of this study is to propose a methodology to identify the quality of three-dimensional printed parts with circular holes in the laser aided additive manufacturing process. We utilize a response surface methodology to represent the relationship between input variables (chord height tolerance and diameter of a hole) and response (geometric error) for evaluating the geometric accuracy of the three-dimensional printed parts with the diameter of holes. From the calculated response surface methodology, we conclude that the proposed methodology can be utilized as a process design guide to guarantee the quality of a part printed from the laser aided additive manufacturing process. The efficiency and limitations of the proposed methodology are verified by conducting a case study.